2017
DOI: 10.1099/jgv.0.000842
|View full text |Cite
|
Sign up to set email alerts
|

The P gene of rodent brain-adapted measles virus plays a critical role in neurovirulence

Abstract: In rare cases, measles virus (MV) in children leads to fatal neurological complications such as primary measles encephalitis, post-acute measles encephalitis, subacute sclerosing panencephalitis and measles inclusion-body encephalitis. To investigate the pathogenesis of MV-induced encephalitis, rodent brain-adapted MV strains CAM/RB and CAMR40 were generated. These strains acquired mutations to adapt to the rodent brain during 40 passages in rat brain. However, it is still unknown which genes confer the neurov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To further confirm the implication of cGAS in antiviral responses during MeV infection in vivo , we used a rodent brain-adapted strain of MeV (MeV-CAMR40) [ 40 , 41 ]. Knockout mice lacking the RNA sensor-related molecule (MAVS) or DNA sensor molecule (cGAS) were intracerebrally inoculated with the virus, and the survival curve was measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the implication of cGAS in antiviral responses during MeV infection in vivo , we used a rodent brain-adapted strain of MeV (MeV-CAMR40) [ 40 , 41 ]. Knockout mice lacking the RNA sensor-related molecule (MAVS) or DNA sensor molecule (cGAS) were intracerebrally inoculated with the virus, and the survival curve was measured.…”
Section: Resultsmentioning
confidence: 99%
“…A72-B cells (canine fibroblast cells; kindly provided from Intervet KK Co. Ltd., Japan) were cultured in Eagle’s minimal essential medium supplemented with 10% FCS and 0.3% triptose phosphate broth. MeV-HL and rMV-EGFP [ 18 ] or MeV-CAMR40 [ 41 ] were infected with B95a cells or Vero cells supplemented with 2% FCS, respectively, and harvested by freeze-thawing and sonication when syncytium formation was at its maximum. Strain RSV-A2 was inoculated into HEp-2 cells supplemented with 2% FCS, and 4 days later cells were harvested together with culture medium and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the time, the viral cycle does not seem compromised but the lower expression level of V could contribute to the viral persistence by reduced inhibition of interferon (IFN) response [134]. Is has also been shown that the P gene of the multi-mutated rodent brain-adapted strain CAMR40 is largely involved in neurovirulence, suggesting that MeV P gene could also play a role in CNS infection [135].…”
Section: Mutations Associated With Mev Cns Infectionmentioning
confidence: 99%